2002
DOI: 10.1038/sj.onc.1206035
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of Cyclin E2 expression and associated kinase activity in primary breast tumors

Abstract: The increased expression of G 1 cyclins has been associated with the many types of human tumors. In primary solid tumors however, the expression and activity of cyclin E2, the newest member of the G 1 cyclin family, is largely unknown. In this study we have analysed the expression of the E-type cyclins in primary solid tumors from breast, lung, uterus, ovary, colon, and rectal tissues. Relative gene expression was analysed by quantitative real-time reverse transcription polymerase chain reaction (Taqman). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
51
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 13 publications
2
51
0
Order By: Relevance
“…Remarkably, although similar methods were used in both these papers (Nielsen et al, 1996;Keyomarsi et al, 2002), Nielsen et al (1996) reported very low to undetectable levels in normal breast tissue. On the other hand, quantitative RT-PCR also indicated that 23% of tumors overexpress cyclin-E compared to normal tissue (Payton et al, 2002). These results also confirm the strong relation between mRNA and protein cyclin-E levels in tumor tissue.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Remarkably, although similar methods were used in both these papers (Nielsen et al, 1996;Keyomarsi et al, 2002), Nielsen et al (1996) reported very low to undetectable levels in normal breast tissue. On the other hand, quantitative RT-PCR also indicated that 23% of tumors overexpress cyclin-E compared to normal tissue (Payton et al, 2002). These results also confirm the strong relation between mRNA and protein cyclin-E levels in tumor tissue.…”
Section: Discussionsupporting
confidence: 75%
“…On the other hand, diminished proteolysis could also be involved in deregulated cyclin-E levels, as described in a breast cancer cell line with high cyclin-E (Strohmaier et al, 2001). Using this method, we confirmed the previously described negative correlation of cyclin-E levels with ER in breast cancer determined by Western blotting, immunohistochemistry, or quantitative RT-PCR (Nielsen et al, 1996(Nielsen et al, , 1997Donnellan et al, 2001;Payton et al, 2002;Ku¨hling et al, 2003). This association of mRNA with protein data concurs with the early observation that gene amplification and increased transcription of cyclin-E is implicated in its overexpression in breast cancer (Keyomarsi and Pardee, 1993).…”
Section: Discussionsupporting
confidence: 73%
“…5,6 Aberration of cyclin/CDK activity is commonly associated with tumor formation. [7][8][9][10] Genomic instability is another key feature of tumorigenesis. Mammalian cells have developed a number of repair systems to combat DNA damage and to maintain genomic integrity.…”
mentioning
confidence: 99%
“…Cyclins E1 and E2 display similar biochemical activities and expression patterns, in terms of both tissue specificity and timing of expression during cell cycle progression (15,18,31,53). Yet there is a precedent for the distinct regulation of either gene, since the papillomavirus oncoprotein E6 was found to stimulate cyclin E2 expression but to repress cyclin E1 (74).…”
Section: Discussionmentioning
confidence: 99%